Evaluation of porphyrin molecules as effective corrosion inhibitors for copper alloy in sulfuric acid using both experimental and computational approaches - Metwally Abdallah; Majda Alfakeer; Rasha N Felaly; Abdulaziz M. Almohyawi; Jabir H. Al-Fahemi; Salih S. Al-Juaid; Doaa F. Seyam; Elsayed M. Mabrouk; Kamal A. Soliman (Journal of Electrochemical Science and Engineering)
The inhibition efficacies of two porphyrin molecules, namely, 5,10,15,20-tetra-[m-(methoxy) phenyl] porphyrin (m-TMPP) and 5,10,15,20-tetra-[p-(methoxy)phenyl] porphyrin (p-TMPP) on the corrosion of copper alloy (C12510) in 1.0 M H2SO4 solutions were examined. Some chemical, electrochemical measurements, density functional theory and Monte Carlo simulations were utilized to study the adsorption behaviour and corrosion inhibition efficiency of m-TMPP and p-TMPP on the Cu (111) surface in acidic media. Scanning electron microscopy analysis was employed to examine the surface morphologies of the tested C12510 surfaces. The outcomes of these techniques proved that the inhibition efficiency increases with increasing concentration of TMPP molecules and with lowering tempera¬tu¬res. The inhibition efficiency is reached to 96.23 and 97.61 % in the case of m-TMPP and p-TMPP, respectively, using the potentiodynamic polarization technique. The inhibitory effect of TMPP molecules is explained based on their spontaneous physicochemical adsorption on the surface of C12510. The adsorption process is obeyed by the Langmuir isotherm model. Additionally, some thermodynamic activation parameters were determined and discussed. It was discovered that the two TMPP compounds retarded the pitting corrosion of C12510 in chloride-containing solutions by shifting the pitting potential to a more noble direction. Based on all the approaches investigated, the inhibitory efficacy of p-TMPP is higher than that of m-TMPP at every concentration tested.